2020
DOI: 10.1016/j.neuropsychologia.2020.107492
|View full text |Cite
|
Sign up to set email alerts
|

Striatal bases of temporal discounting in early adolescents

Abstract: Steeper rates of temporal discounting-the degree to which smaller-sooner (SS) rewards are preferred over larger-later (LL) ones-have been associated with impulsive and ill-advised behaviors in adolescence. Yet, the underlying neural systems remain poorly understood. Here we used a well-established temporal discounting paradigm and functional MRI (fMRI) to examine engagement of the striatum-including the caudate, putamen, and ventral striatum (VS)-in early adolescence (13-15 years; N=27). Analyses provided evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…DD tasks activate the default mode, frontoparietal, salience, and reward network brain regions in healthy adults (for review see Frost and McNaughton, 2017 ), with similar patterns in typically developing youth ( de Water et al, 2017 , Hamilton et al, 2020 ). The only study to date that examined DD activation in youth FH positive for SUD found no differences compared to FH negative youth ( Rodriguez-Moreno et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…DD tasks activate the default mode, frontoparietal, salience, and reward network brain regions in healthy adults (for review see Frost and McNaughton, 2017 ), with similar patterns in typically developing youth ( de Water et al, 2017 , Hamilton et al, 2020 ). The only study to date that examined DD activation in youth FH positive for SUD found no differences compared to FH negative youth ( Rodriguez-Moreno et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, because we were estimating the location of effects rather than the size of effects, there was no statical penalty for reported null reports. To this end, it is worth nothing that a large number of studies that used the choice contrast (LLR, SSR) reported no significant clusters for this contrast 20,31,43,48,50,56,58,[63][64][65][66][67][68][69][70] , whereas only two studies reported no significant effects of SV 71,72 . This comparison further highlights the importance for identifying and implementing more reliable analytic strategies for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Modulation of pre-SMA activity resulted in the prevention of behavioural expression of impulsive actions without effect on their generation [ 54 ]. Consequently, greater connectivity of pre-SMA with the ventral striatum could result in superior motor control over the reward system, as higher activity of the ventral striatum predicted impulsive choices in HC [ 55 ].…”
Section: Discussionmentioning
confidence: 99%